Teacher Implementation of College- and Career-Readiness Standards: Links Among Policy, Instruction, Challenges, and Resources - Adam K. Edgerton; Laura M. Desimone (SAGE Publishing, 2018)
Using state-representative teacher surveys in three states-Texas, Ohio, and Kentucky-we examine teachers' implementation of college- and career-readiness (CCR) standards. What do teachers report about the specificity, authority, consistency, power, and stability of their standards environment? How does their policy environment predict standards-emphasized instruction? Do these relationships differ for those who teach different subjects (math and English Language Arts [ELA]), different grades (elementary or high school), different populations (English Language Learners [ELLs], students with disabilities [SWDs]), and in different areas (rural, urban, or suburban)? We found elementary math teachers taught significantly more standards-emphasized content than elementary ELA teachers, whereas secondary ELA teachers taught significantly more standards-emphasized content than secondary math teachers. Teachers of SWDs and rural teachers taught significantly less of the emphasized content. In all three states, we found greater buy-in (authority) predicted increased emphasized content coverage among ELA teachers but not among math teachers.